EFFECT OF LONG-TERM USE OF PROTON PUMP INHIBITORS ON THE CONTENT OF NITRITE IONS IN THE BLOOD SERUM AND MUCOUS COATING OF THE GASTROINTESTINAL TRACT OF RATS - Dubinin, S.I.; Hryniova, M.V.; Novopysmenny, S.A.; Homlia, L.M.; Diachenko-Bogun, M.M.; Shkura, T.V.; Makarchuk, V.V. (World of Medicine and Biology, 2023)
The purpose of the study was to determine the content of nitrite ions in blood serum and mucous membranes of the stomach and colon in rats under the conditions of long-term use of proton pump inhibitors Omeprazole and Pantoprazole. The study was performed on 30 white non-linear male rats, divided into three groups. The control (first group) received water for injections intraperitoneally once a day for 28 days. The second – Omeprazole. The third – Pantoprazole. After long-term administration of omeprazole and pantoprazole, the concentration of NO2- in blood serum increased by 24 % (p
Keywords: hypochlorhydria; pantoprazole; omeprazole; inflammatory process